การบริหารแบบมีส่วนร่วมสู่การเป็นโรงเรียนส่งเสริมสุขภาพระดับเพชร สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี - ทองที, ศิริชัย; ชมภูวิเศษ, พัชรินทร์; เพ็งจันทร์, ธีระพล (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 3 (2567): กันยายน-ธันวาคม 2567, 2024)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ ศึกษากระบวนการบริหารแบบมีส่วนร่วมสู่การเป็นโรงเรียนส่งเสริมสุขภาพระดับเพชร สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาอุดรธานี กรณีศึกษาโรงเรียนบ้านโชคเจริญ ใช้ระเบียบวิธีวิจัยเชิงคุณภาพ กลุ่มผู้ให้ข้อมูลหลัก จำนวน 10 คน ได้แก่ ผู้บริหารสถานศึกษา จำนวน 1 คน หัวหน้ากลุ่มงาน จำนวน 2 คน ครูผู้รับผิดชอบงานส่งเสริมสุขภาพของโรงเรียน จำนวน 3 คน ผู้ทรงคุณวุฒิ จำนวน 2 คน และเจ้าหน้าที่สาธารณสุขในพื้นที่ จำนวน 2 คน เครื่องมือที่ใช้ในการวิจัย ประกอบด้วย 1) แบบสัมภาษณ์กึ่งโครงสร้าง 2) แบบสังเกตบริบทของโรงเรียน และ 3) แบบวิเคราะห์เอกสาร เก็บรวบรวมข้อมูลการสัมภาษณ์ การสังเกต และการวิเคราะห์เอกสาร ตรวจสอบข้อมูลแบบสามเส้าเพื่อยืนยันความเที่ยงตรงและความเชื่อมั่นของข้อมูล ผลการวิจัยพบว่า การบริหารแบบมีส่วนร่วมสู่การเป็นโรงเรียนส่งเสริมสุขภาพระดับเพชร ใช้กระบวนการบริหารแบบมีส่วนร่วมในการดำเนินงานโรงเรียนส่งเสริมสุขภาพระดับเพชร จากผู้ที่มีส่วนได้เสีย ได้แก่ ผู้บริหาร ครู นักเรียน บุคลากรทางการศึกษา คณะกรรมการสถานศึกษา ผู้ปกครองนักเรียน ผู้นำชุมชน อาสาสมัครสาธารณสุขประจำหมู่บ้าน กลุ่มแม่บ้าน องค์การบริหารส่วนตำบล โรงพยาบาลส่งเสริมสุขภาพตำบล สาธารณสุขอำเภอ โรงโม่หิน ร่วมกันประชุมวางแผนเพื่อวิเคราะห์สภาพปัจจุบันของโรงเรียน ใช้เป็นฐานข้อมูลในการกำหนดนโยบาย เป้าหมาย วิสัยทัศน์ พันธกิจ เอกลักษณ์ อัตลักษณ์ ศึกษาวิเคราะห์องค์ประกอบ ตัวชี้วัด และเกณฑ์มาตรฐานการประเมินโรงเรียนส่งเสริมสุขภาพระดับเพชร ออกแบบกิจกรรม กำหนดขอบข่ายงาน บทบาทหน้าที่และผู้รับผิดชอบอย่างชัดเจน ผู้บริหารมีสมรรถนะในการสื่อสารที่ดี สามารถจูงใจให้ทุกฝ่ายร่วมดำเนินงานด้วยความเต็มใจ ถ่ายทอดแผนงานลงสู่การปฏิบัติจริง โรงเรียนดำเนินงานอย่างรอบด้าน อาทิ การจัดการเรียนรู้ในชั้นเรียน ระบบดูแลช่วยเหลือนักเรียน พัฒนาสิ่งแวดล้อมและแหล่งเรียนรู้ในโรงเรียน สุขอนามัยของนักเรียน โภชนาการอาหาร ระบบสุขาภิบาล ความสะอาดและน้ำดื่ม ผู้บริหารและผู้รับผิดชอบโครงการเป็นผู้มีบทบาทหลักในการกำกับ ควบคุม ติดตามความก้าวหน้าของงานคณะกรรมการสถานศึกษา ผู้ปกครอง ชุมชน นักเรียน ช่วยสนับสนุนทรัพยากร งบประมาณ กำลังคนในการพัฒนาโรงเรียน ประเมินผลการดำเนินงานทั้งระบบอย่างมีประสิทธิภาพ คือ การเป้าหมาย  การวางแผนงาน การดำเนินงานและผลลัพธ์ จากการดำเนินงานด้านสุขภาพอย่างต่อเนื่อง ทำให้นักเรียนมีสุขนินิสัยที่ดี มีสุขภาพร่างกายเข็งแรง เรียนรู้อย่างมีความสุข พัฒนาการเหมาะสมตามวัย และใช้ชีวิตร่วมกับผู้อื่นได้อย่างมีความสุข The objectives of this research were: Study the participatory management process toward becoming a diamond-level health-promoting school under the Udonthani Primary Education Service Area Office. A case study of Ban Chok Charoen School. Use qualitative research methodology. Target group of 10 key informants, 1 administrator school, 2 group leaders, 3 teachers of school's health, 2 experts, and 2 public health officers. The research tools include 1) Semi-structured interview form, 2) School context observation form, and 3) Document analysis form. Data collection involved interviews, observations, and document analysis, with triangulation of data to ensure validity and reliability of the information. The results of the research were as follows: The participatory Management Process to be health promoting at diamond level school. Employs a participatory management approach in the implementation of diamond level health delivery schools. This process involves stakeholders including Administrators, Teachers, Students, Educational personnel, The school board, Parents, Community leaders, Village public health volunteers, Housewives groups, Subdistrict Administrative Organization, Dental Officer, Subdistrict Health Promotion Hospital, District Public Health Officer and Stone Mill. Together have a planning meeting to analyze the current condition of the school. This assessment will serve as a database for formulating policies, goals, visions, missions, and identity. Examine and analyze the elements, indicators, and benchmarks for the evaluation of diamond-level health promotion schools to design activities and scope of work, Roles, Duties, and responsibilities will be distinctly outlined. The administrators possess strong communication skills, effectively motivating all parties to collaborate willingly and translating plans into actionable practices. The school operates comprehensively across all aspects, such as: Classroom learning management, Student support systems, Development of environments and learning resources in schools, Student hygiene, Food nutrition, Sanitation systems, Cleanliness, and Drinking water. The administrators and teacher are integral to supervising, controlling, and monitoring the progress of the school board, parents, community, and students. They provide support for resources, budgets, and manpower in school development and effectively evaluate the overall system's performance, including goal setting, planning, operations, and results from ongoing health initiatives. This enables students to cultivate good habits, maintain physical health, engage joyfully in learning, develop appropriately for their age, and live happily with others.